The Application of the Mind Mapping Learning Method on Student Learning Outcomes - Nadia Permata Sari; Mesterjon Mesterjon; Jumiati Siska (Jurnal Komputer Indonesia, 2026)
This study aims to describe the application of the Mind Mapping learning method and to determine its impact on the learning outcomes of 10th-grade Visual Communication Design (VCD) students at SMK Negeri 03 Kepahiang regarding the topic of types of cameras. This study was motivated by the low learning outcomes of students, which were caused by a teaching approach still dominated by lectures; as a result, students were less active, had difficulty organizing their ideas, and lacked an understanding of the relationships between concepts in the material. This study employed a descriptive qualitative approach. The research subjects were 14 10th-grade VCD students at SMK Negeri 03 Kepahiang. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. Data validity was tested using source triangulation and technique triangulation. The results of the study indicate that the implementation of the Mind Mapping method occurred through the stages of material delivery, group formation, mind map creation, presentation of work results, and learning reflection. During the learning process, students were observed to be more active in discussing, asking questions, and presenting their group work. The use of colors, symbols, images, and keywords in Mind Mapping helped students understand the material more easily and in a structured manner. Student learning outcomes also improved, as evidenced by the average score of 63.64 before the method was implemented, which rose to 81.00 after implementation—an increase of 17.36 points. In addition, all students achieved mastery of the material. Thus, the Mind Mapping method is effective in improving student learning outcomes, engagement, and motivation.